Empowerment of Civil Society and the Army in Collaborative Innovation for Emergency Bridge Construction Due to Flash Floods in Bima NTB - Toni Yuliyanto; Rachma Fitriati (GoAcademica Research & Publishing, 2023)
This article aims to analyse the empowerment of civil society and the Indonesian Army in collaborative innovation for the construction of an emergency bridge due to flash floods in Bima Regency, West Nusa Tenggara (NTB), in 2021. The flash flood had destroyed the bridge, which was the connecting access to the district market as the center of the community's local economy. The soft systems methodology (SSM) approach analyzed the complex situation involving various human activity systems in the bridge construction collaboration. The analysis results show the need for collaborative innovation between the Provincial and District Governments, Non-Government, the Indonesian National Army (TNI), the Indonesian National Police (Polri), and civil society. Especially in disaster emergency conditions, the choice of Ultra-Wide Acrow Panel Bridge technology proposed bottom-up by the NTB Provincial Government and the Military Resort Command (Korem) 162/Wira Bhakti NTB proved to be faster, more practical and more robust than the Bailey Bridge technology by the Ministry of Public Works and Public Housing of the Republic of Indonesia (Kemen PUPR RI). This collaborative innovation restored road connectivity and the local economy and improved the quality of public services in Bima District. The contribution of this article is to provide enrichment about learning collaborative innovation in disaster management efforts and bottom-up infrastructure development in disaster situations.